Formulasi dan Potensi Antibakteri Mouthwash Infusa Bunga Mawar Merah (Rosa Damascena Mil) Melalui Uji Organoleptik dan Uji pH - Ananda, Reva Dwi; Khoirunnisa, Safitri Nur; Trisnawati, Sella; Purboastuti, Sindy Arum (Ridwan Institute, 2025)
Dental caries, especially caused by the bacteria Streptococcus mutans, is a common oral health problem. Long-term use of synthetic chemical mouthwashes poses health risks, prompting the search for safe and effective natural alternatives. This study aims to formulate and evaluate the antibacterial potential of red rose infusion mouthwash (Rosa damascena Mill) through organoleptic tests and pH tests. Red rose infusion is made and formulated into three mouthwash preparations with different infusion concentrations (5%, 10%, and 15%), using additives such as sodium benzoate, glycerin, Tween 80, oleum menthae piperitae, 70% ethanol, and aquadest. Organoleptic testing includes the observation of color, aroma, and clarity, while pH testing is performed to ensure the safety of the preparation. The antibacterial activity test was carried out using the inhibition zone measurement method. The results of organoleptic tests show color variations from yellow to clear peach with a distinctive mint mixed with rose aroma, as well as good clarity in all formulations. The pH test results showed that the three formulations were within the physiological pH range of the oral cavity (6.0–7.5), namely 6.78 (5%), 6.45 (10%), and 6.11 (15%), so they were safe to use. However, the antibacterial activity test showed that only formulations with an infusion concentration of 5% had an inhibition zone (6.56 mm), while concentrations of 10% and 15% showed no antibacterial activity. This is in contrast to the literature that states that higher concentrations of rose extract can result in larger barrier zones.